Autokorelasi Silang Return Saham Perusahaan Besar dan Perusahaan Kecil di Bursa Efek Jakarta - Noor Endah Cahyawati (Jurnal Akuntansi dan Auditing Indonesia, 2003)
The objective of this study is to examine to what extent lagged large firm return can pre¬dict current small firm returns. Samples include all Jakarta Stock Exchange’s companies that re¬lease their annual financial statements (net income) during January-July in 1998, 1999, 2000, 2001 and 2002.The results of this study: First, lagged large firm return granger cause to current small firm returns. Thus, lagged large firm returns contain predictive power over current small firm re¬turns. Second, size based portfolio return cross-autocorrelations is significantly different in up and down markets but there is no directional asymmetry. Third, cross-autocorrelations coefficient is significantly different when portfolio returns become more synchronous. Fourth small firm returns autocorrelations have no effect significantly to the returns cross-autocorrelations. Fifth, small firm respond common information much more slowly than large firm. This study also finds that small firm responds good news much more slowly than large firm but respond bad news without a delay.